Mauqi’ Learn Arabic Online: Wasilah At-Ta’lim li Tahsini Itqani Al-Mufradat Al-Lughah Al-Arabiyah - Rofi'i, M.; Roziqin, Ahmad Hoirur (STAI Syaichona Moh. Cholil Bangkalan, 2024)
Vocabulary acquisition is a crucial part of language learning, and improving vocabulary mastery in the Arabic language is important for students, particularly in high schools. In this context, the Learn Arabic Online platform has emerged as a digital educational tool aimed at enhancing students' ability to master Arabic vocabulary. This study aims to explore the effectiveness of the Learn Arabic Online platform as an educational tool for improving Arabic vocabulary mastery among tenth-grade students at Al-Ghazali High School in Arosbaya, Bangkalan, by analyzing students' experiences, perceptions, and challenges while using the platform. The researcher used a qualitative descriptive approach to collect data through observations, documentation, and in-depth interviews with several tenth-grade students who participated in vocabulary learning through the platform. The data was analyzed using Miles and Huberman’s data analysis method, which includes data reduction, data display, and conclusion drawing. The results showed that the Learn Arabic Online platform significantly helped students improve their mastery of Arabic vocabulary. Students reported that the interactive features and educational materials provided through the platform effectively supported their learning process. However, some challenges were identified, such as the lack of direct interaction with the teacher and the need for high levels of self-discipline. The study concluded that Learn Arabic Online is an effective educational tool for improving Arabic vocabulary mastery among tenth-grade students at Al-Ghazali High School in Arosbaya, Bangkalan.